2021
DOI: 10.1016/j.ajoc.2021.101180
|View full text |Cite
|
Sign up to set email alerts
|

Epiretinal membrane-induced intraretinal neovascularization

Abstract: Purpose To report a 71-year-old male patient diagnosed with epiretinal membrane-induced intraretinal neovascularization. Observations The presence of an epiretinal membrane (ERM) was confirmed by Optical Coherence Tomography (OCT), fluorescein and indocyanine angiography. Optical coherence tomography angiography (OCT-A) revealed a neovascular membrane within the ERM. Intravitreal ranibizumab injections were administered three times at four-week intervals. Imaging reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…8 Giachos et al reported a case of a 71-year-old male who presented with an ERM, a subhylaoid and intraretinal hemorrhage which was confirmed using multimodal imaging and described its treatment response with intravitreal Ranibizumab. 9 Lee et al in their report have described an ERN in a patient with RP and have shown reduction in vascularity post treatment with intravitreal bevazizumab. 10…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…8 Giachos et al reported a case of a 71-year-old male who presented with an ERM, a subhylaoid and intraretinal hemorrhage which was confirmed using multimodal imaging and described its treatment response with intravitreal Ranibizumab. 9 Lee et al in their report have described an ERN in a patient with RP and have shown reduction in vascularity post treatment with intravitreal bevazizumab. 10…”
Section: Discussionmentioning
confidence: 96%
“…8 Giachos et al reported a case of a 71-year-old male who presented with an ERM, a subhylaoid and intraretinal hemorrhage which was confirmed using multimodal imaging and described its treatment response with intravitreal Ranibizumab. 9 Lee et al in their report have described an ERN in a patient with RP and have shown reduction in vascularity post treatment with intravitreal bevazizumab. 10 Ayachit et al described ERN in seven eyes of four patients with Mac Tel 2 and with six of the seven eyes showing a communication with the intraretinal vascular network and with none of the eyes showing MNV.…”
Section: Np56mentioning
confidence: 96%
“…Giachos et al declared that it is feasible that intraretinal neovascularization in an idiopathic ERM occurred because of, or near, preexisting ERMs. Initially, they considered a perimacular branch retinal vein occlusion, a congenital retinal anomaly, an age-related macular degeneration (AMD) lesion, and macular telangiectasia as differential diagnoses [ 7 ]. However, they were ultimately ruled out until IVEM was the final diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Managing IVEM can be challenging. Since it a rare, the only published case reports had different follow-up periods and treatment approaches that incorporated observation, anti-VEGF therapy, vitrectomy, and combined treatment [ 2 , 3 , 5 7 ]. Therefore, treatment outcomes may vary.…”
Section: Discussionmentioning
confidence: 99%
“…One of the phenomena observed in the course of PDR is capillary oclusion in the retina, which, by causing hypoxia, increases the expression of VEGF by the cells that build the retina (32). Pathological retinal angiogenesis promotes the formation of subretinal hemorrhages, which in turn promotes the development of ERM (33).…”
Section: Cytokine or Molecule Descriptionmentioning
confidence: 99%